Cultural Competency Development in Pre-Service Teachers: A Transformative Learning Experience Mode - Mengxue, Zhao; Yicheng , Lin; Ziqiang, Luo (Mutiara Intelektual Indonesia Press, 2025)
The cultural competency has emerged as a critical component in teacher preparation, addressing the challenges of increasingly diverse educational landscapes. Despite its recognized importance, there remains a significant gap in standardized approaches to developing cultural competence among pre-service teachers. This study aimed to investigate the transformative potential of cultural competency development among pre-service teachers through a comprehensive mixed-methods approach, seeking to explore how structured interventions can enhance educators' ability to recognize, understand, and respond to cultural nuances in classroom settings. Employing a mixed-methods sequential explanatory design, the study involved 120-150 pre-service teachers selected through purposive sampling. The research utilized multiple data collection instruments, including pre- and post-intervention surveys, reflective interviews, journals, and observational field notes. The intervention combined reflective practices, critical dialogue, and experiential learning experiences. Previous research lacked a comprehensive framework for cultivating cultural competency that simultaneously addresses cognitive, emotional, and practical dimensions of cultural understanding. The study offers a transformative model for teacher preparation, positioning cultural competency as a fundamental cornerstone of effective, equitable education. The research revealed remarkable improvements across three critical dimensions: Cognitive Awareness (78.3% enhancement), Affective Responsiveness (90.5% improvement), and Behavioral Adaptability (77.3% progression). Overall cultural competency demonstrated an 81.8% statistically significant improvement. The research illuminates cultural competency as a dynamic, continuous process of learning and growth. It challenges traditional educational paradigms by providing a holistic approach to preparing educators who are genuinely responsive to diverse cultural contexts, ultimately contributing to a more inclusive and equitable educational landscape